AI and Augmented Reality (AR) in Transforming Interactive Media Experiences: Conceptualizing the Future of Immersive Content - Chigozie Emmanuel Benson,; Chinelo Harriet Okolo,; Olatunji Oke, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper explores the transformative role of Artificial Intelligence (AI) and Augmented Reality (AR) in reshaping interactive media experiences. It examines how these technologies enhance personalization, enable immersive storytelling, and facilitate seamless cross-platform integration, revolutionizing the creation and consumption of content. Recent technological advancements, such as machine learning and spatial computing, are identified as key enablers of this transformation. The paper also discusses challenges, including ethical concerns, accessibility barriers, and technological limitations, emphasizing the importance of stakeholder collaboration to address these issues. By conceptualizing future trends, such as virtual humans and adaptive environments, and providing a framework for understanding user engagement, this study highlights the potential of AI and AR to redefine interactive media across industries, including entertainment, education, and marketing. Recommendations for researchers, content creators, and policymakers focus on fostering innovation while ensuring ethical practices and accessibility.
Keywords: Artificial Intelligence; Augmented Reality; Interactive Media; Immersive Content; Personalization; Cross-Platform Integration